Participation of directors in Corporate Directors Training Program (CDTP): A study of non-listed companies in Kedah - Othman, Zaleha; Mat Noh, Masanita (2005)
Participation of directors in Course Directors Training Program (CDTP) is important in order to enhance awareness and understanding of corporate governance and more importantly to enhance awareness of corrupt practices as has happened in many giant organizations in recent years.CDTP is an approached to improve directors knowledge towards corporate compliance.Therefore this study is conducted to determine the participation among directors of non listed companies in Kedah in CDTP.The study hope to shed some light for authority such as Companies Commission of Malaysia to take further action in encouraging directors to attend the training.